Generalized Trust and Financial Risk-Taking in China – A Contextual and Individual Analysis - Xu, Yi (Frontiers in Psychology, 2018)
Previous evidence from developed nations has suggested that more trusting individuals are more likely to take financial risks, such as investing in the stock market. Previous studies have found that Chinese citizens have particularly high generalized trust and are more risk-seeking in investment compared with Americans, which makes China an interesting case. The current study examines the relation between generalized trust and stock market participation in China at both a contextual and individual level. Across provinces, a lower level of generalized trust was associated with stock market participation. For example, the stock market participation was four times higher in provinces with the lowest level of perceived fairness than in provinces with the highest level of perceived fairness. The contextual effects of less generalized trust suggest an association between risk- taking behaviors and societal level inequality. At the individual level, trust of strangers was associated with risk preference in highly educated and wealthy people but its effect on risk behaviors was not clear. The findings suggest that trust may affect financial risk-taking behavior at different levels through different pathways, and that cultural differences in understanding of trust also need to be considered.